2015
DOI: 10.4238/2015.april.22.3
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the prevention of hospital-acquired infection through standardized teaching ward rounds in clinical nursing

Abstract: ABSTRACT. This study aimed to explore the effect of standardized teaching ward rounds in clinical nursing on preventing hospital-acquired infection. The experimental group comprised 120 nursing students from our hospital selected between June 2010 and June 2012. The control group consisted of 120 nursing students selected from May 2008 to May 2010. Traditional teaching ward rounds for nursing education were carried out with the control group, while a standardized teaching ward round was carried out with the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
2
6
0
1
Order By: Relevance
“…In line with our results, Zhang (2015) found in an experimental study, conducted in Shanghai with 120 nursing students who participated in teaching rounds and another 120 students in the control group who had practical placements as per the traditional model, that teaching rounds increased students' knowledge, which in Zhang's study was focused on nosocomial infections [14]. The results of a study conducted in Cuba, albeit in medicine, also demonstrated that the teaching round allows the student to develop clinical skills using immediate feedback with critique and self-critique, and that it fosters the development of their own criteria [15].…”
Section: Discussionsupporting
confidence: 92%
“…In line with our results, Zhang (2015) found in an experimental study, conducted in Shanghai with 120 nursing students who participated in teaching rounds and another 120 students in the control group who had practical placements as per the traditional model, that teaching rounds increased students' knowledge, which in Zhang's study was focused on nosocomial infections [14]. The results of a study conducted in Cuba, albeit in medicine, also demonstrated that the teaching round allows the student to develop clinical skills using immediate feedback with critique and self-critique, and that it fosters the development of their own criteria [15].…”
Section: Discussionsupporting
confidence: 92%
“…Im Rahmen eines solchen Interventionsprogramms haben Fortbildungen insbesondere in standardisierter Form [373] und Training [374] eine Schlüsselfunkti-on, jedoch als alleinige Interventionsmaß-nahme nur einen geringen, kurz anhaltenden Effekt [132,370,371,375].…”
Section: Technikunclassified
“…Five of the six studies were undertaken in the university setting (Jeffries et al, 2002; Melby et al, 1997; O'Neill, 2001; Walsh et al, 2011; Wright et al, 2008). One study (Zhang, 2015), took place in clinical practice.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in Uysal's (2016) retrospective, analytical study of nursing students' practical skills examination papers (n = 605), failure to adhere to the principles of asepsis was the most common mistake (21.3%, 18.9%, 45.3%) over a three-year period. (Rush et al, 2014;Uysal, 2016;Wright et al, 2008) or skill tests (91.7%-100%) (Jeffries et al, 2002;Zhang, 2015) by students was reported across other observational studies and intervention studies reported under objective 1.…”
Section: Competencymentioning
confidence: 94%